Filogeografia comparativa e história demográfica de dois marsupiais da Mata Atlântica - Zanchetta, Letícia Sartorato (2014)
The Atlantic Forest isa biodiversityhotspot and has been the focus of many researchprojectsbecause it is a complex yetpoorly understood biogeographical unit. Comparative phylogeographic studieshave been playingan important role on biodiversity knowledge,since the comparisonsamong different taxa allow the investigationof fundamental links between population processes and regional patterns of diversity and biogeography. Therefore,here Iinferred and compared the demographic and biogeographic histories of two Atlantic Forestmarsupialspecies,Gracilinanusmicrotarsus andMarmosopsincanus,to find outhowthey responded to environmental changes over the time. Sequences of the mitochondrial cytochrome b and D-loopgeneswere used for phylogeneticreconstruction, haplotype network andpopulation genetic analyses. The results showed high genetic divergence inboth species, as well strong geographic structure,with similar geographically cohesivegroups in both species. The distinctiveness ofhaplotypesfrom the southernAtlantic Forest was also observed in the phylogenies,and is consistent with geographic barriers such as Serra do Mar and Rio Paraíba do Sul, for example.Theoldest intraspecific clades originated in the Neogene, which isconsistent witha period of climaticchangesand intense tectonic events, indicating that thepopulation genetic structure of bothspecies is the result of processes that occurredlong before the Pleistocene.Theeffective population size fluctuations of G. microtarus and M. incanusweresimilar, mostlyfrom the last glacialmaximum21,000 years ago. Thus,the data indicate that changes in theenvironment over time generatedsimilar phylogeographic anddemographicstructures in these two marsupials species, resulting from acommon biogeographic history in the Atlantic Forestin the last 7 million years,while recent environmental changeswere unable toaffect the demographyof the species,contrary to expectationsbased on ecological responses from G. microtarsus e M. incanusto the habitatreduction and fragmentation